Simulation‑based architecture of a stable large‑area JDBD atmospheric plasma source - M.V., Roshan; S., Razaghi; A., Singh (Springer Nature, 2023)
Unified jet‑DBD design, JDBD , proposed in this work presents large‑scale plasma in an unbounded region of atmospheric air, without any need for the flow of gas, offering efficient exposure to sizable and complex objects. This is a simulation‑based architecture for stable non‑thermal plasma source with notable experimental results. JDBD geometry optimizes the electric field and charge distribution for a diffuse discharge in the steady air by a key design parameter of efficient insulation. Teflon insulator with a thickness dTf ≥ 10 mm imposes an intense and uniform electric field shaped up at the open area in front of the device and generates radially/axially expanded plasma jet. In the JDBD , phase shift increases by Irms and the plasma generates more power than the classical plasma jet. Two distinct states of JDBD operation indicate the mode‑swap at 0.8 mA and power dissipation. In the reactive JDBD scheme even small changes in the phase angle effectively improves the electric power.